2013
DOI: 10.3389/fmicb.2013.00355
|View full text |Cite
|
Sign up to set email alerts
|

Bespoke microbiome therapy to manage plant diseases

Abstract: Information gathered with advanced nucleotide sequencing technologies, small molecule detection systems and computational biology is revealing that a community of microbes and their genes, now termed “the microbiome,” located in gut and rhizosphere, is responsible for maintaining the health of human beings and plants, respectively. Within the complete microbiome a “core-microbiome” exists that plays the pivotal role in well being of humans and plants. Recent studies in medicine have shown that an artificial mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 65 publications
0
52
0
2
Order By: Relevance
“…Such a final cross-factoring experiment of microbiomes that were artificially selected under different treatments (see Experimental Contrasts, Box 3) can also be a powerful approach to test whether microbiomes evolved with Method 1 have treatment-specific effects on a host. A new research horizon in medicine and agriculture aims to improve animal and plant performance by altering their microbiomes [28,31,32]. Towards this end, a novel and underutilized approach employs artificial selection on a host-microbial association to engineer microbiome function [33,34], a process that we term host-mediated microbiome selection, or more simply microbiome engineering (Boxes 2 and 3).…”
Section: Methods 2: Selection Upon Hosts In Diverging Microbiomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a final cross-factoring experiment of microbiomes that were artificially selected under different treatments (see Experimental Contrasts, Box 3) can also be a powerful approach to test whether microbiomes evolved with Method 1 have treatment-specific effects on a host. A new research horizon in medicine and agriculture aims to improve animal and plant performance by altering their microbiomes [28,31,32]. Towards this end, a novel and underutilized approach employs artificial selection on a host-microbial association to engineer microbiome function [33,34], a process that we term host-mediated microbiome selection, or more simply microbiome engineering (Boxes 2 and 3).…”
Section: Methods 2: Selection Upon Hosts In Diverging Microbiomesmentioning
confidence: 99%
“…Third, the taxonomic makeup of microbiomes can be experimentally manipulated to test hypotheses about microbiome function. For example, gnotobiotic hosts can be maintained with a defined set of microorganisms, and microbiomes can be manipulated with antibiotic treatments or transfer of microbiomes between hosts [25][26][27][28][29]. With any of these approaches, it remains challenging to elucidate specific functional roles of the microbiome in shaping host performance traits (e.g., growth, health, enemy deterrence, mate attraction, fertility, and overall fitness).…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Massart et al (2015a) suggested the use of microbiota-derived products or the microbiota itself, directly or indirectly, to develop novel tools for the protection of plants against pathogens. An initial approach could be the use of a synthetic or natural consortium (Gopal et al, 2013) that could be applied to a harvested commodity to see if it results in better disease control due to the expression of a variety of modes of action against the pathogen. Maintaining the right balance and diversity inside the consortium before and after its application, however, may prove to be difficult.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%
“…Plants Native root-associated microbiota transplant [33,34] Inhibit plant diseases, resist environmental stresses, promote growth…”
Section: Microbiome Transfermentioning
confidence: 99%